Global sourcing of family firms - Daniel Horgos (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2010)
In Europe, a huge share of firms is family owned. Since family firms are known to be more risk averse concerning international transactions, an interesting question emerges: Do family firms adopt a different international sourcing pattern. Altering the Gloubal Sourcing model of Antràs and Helpman, this theoretical contribution adopts a family firm's perspective. The model shows that family firms tend to decrease international procurement. In the headquarter intensive sector, where FDI coexists with international outsourcing, family firms unambiguously decrease FDI, whereas the effect on international outsourcing is ambiguous: A substitution process may work towards an increase in international outsourcing activities.
urn:nbn:de:gbv:705-opus-27431
Keywords: F10; D23; L23; 330; Global Sourcing; Family Firms; Outsourcing; Offshoring; FDI; Familienunternehmen; Globalisierung; Outsourcing; Auslandsverlagerung; Theorie